Food and feed safety systems and analysis - Ricke, Steven C., 1957-; Atungulu, Griffiths Gregory; Rainwater, Chase E.; Park, Si Hong (Academic Press, 2018)
Food and Feed Safety Systems and Analysis discusses the integration of food safety with recent research developments in food borne pathogens. The book covers food systems, food borne ecology, how to conduct research on food safety and food borne pathogens, and developing educational materials to train incoming professionals in the field. Topics include data analysis and cyber security for food safety systems, control of food borne pathogens and supply chain logistics. The book uniquely covers current food safety perspectives on integrating food systems concepts into pet food manufacturing, as well as data analyses aspects of food systems.